Clinical characteristics and evaluation of the incidence of cryptococcosis in Finland 2004-2018 - Toivonen Anne; Eriksson Mari; Friberg Nathalie; Hautala Timo; Kääriäinen Sohvi; Leppäaho-Lakka Jaana; Mikkola Janne; Nieminen Tuomas; Oksi Jarmo; Salonen Juha H; Suomalainen Pekka; Vänttinen Markku; et al. (TAYLOR & FRANCIS LTD, 2022)
Background: Cryptococcosis is one of the major causes of mortality among HIV patients worldwide. Though most often associated with late stage HIV infection/AIDS, a significant number of cases occur in other immunocompromised patients such as solid organ transplant recipients and patients with hematological malignancies. Immunocompromised patients are a heterogeneous group and their number increases constantly. Since little is known about the incidence and the clinical features of cryptococcosis in Northern Europe, our aim was to investigate the clinical characteristics of cryptococcosis patients in Finland.
Methods: We retrospectively reviewed the laboratory confirmed cryptococcosis cases in Finland during 2004-2018. Only those who were treated for cryptococcosis were included in the study. Initial laboratory findings and medical records were also collected.
Results: A total of 22 patients with cryptococcosis were included in our study. The annual incidence of cryptococcosis was 0.03 cases per 100,000 population. Ten patients were HIV-positive and 12 out of 22 were HIV-negative. Hematological malignancy was the most common underlying condition among HIV-negative patients.
Conclusions: To our knowledge, this is the first study of the clinical presentation and incidence of cryptococcosis in Finland. We demonstrate that invasive cryptococcal infection occurs not only in HIV/AIDS patients or otherwise immunocompromised patients but also in immunocompetent individuals. Even though cryptococcosis is extremely rare in Finland, its recognition is important since the prognosis depends on rapid diagnostics and early antifungal therapy.